PENGARUH TINGKAT SUKU BUNGA, LEVERAGE, PROFITABILITAS, DAN LIKUIDITAS TERHADAP RETURN SAHAM: Studi Pada Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia - Ni Putu Widiastuti; Surya Nugraha; Kadek Nanik Arismawati (Universitas Triatma Mulya, 2022)
This study aims to analyze the influence of interest rates, leverage, profitability, and liquidity. This research was conducted at the Indonesia Stock Exchange in Banking Sector companies. The research design used in this study is quantitative. The sample uses the Purposive Sampling formula, namely 30 issuers, which are included in the banking sector companies that go public on the Indonesia Stock Exchange with an observation period of 3 (three) years from 2018 to 2020, so the amount of data used is 90 data. The analysis technique in this study used descriptive-comparative statistics, namely: the classical assumption test, multiple linear regression analysis, and the goodness of fit test. The results of the analysis show that 1) the interest rate has no effect on stock returns. 2) leverage has a positive and significant effect on stock returns. 3) profitability has a positive and significant effect on stock returns. 4) liquidity has a positive and significant effect on stock returns. This research provides considerations to investors in investing in the Indonesia Stock Exchange, especially in the banking sector.